Model Kepemimpinan Kepala MIN 1 dan MIN 2 Sekota Samarinda - Darmawati, Darmawati (SYAMIL: Journal of Islamic Education, 2016)
The purpose of this study was to determine the model of leadership Elementary School as the city of Samarinda. Leadership headmaster headmaster said tobe successful if it can truly reflect the values of the expected personality  headmaster, in carrying out their duties do not conflict with applicable regulations, and the results reflect the achievement of a balance between the objectives of madrasas, the purpose of the existing human resources in madrasas, as well as the desires or expectations of society. Leadership headmaster can also be interpreted as a model or a variety of leadership headmaster appropriate to the situation in order to influence, to direct, guide to sub ordinates by streng thening confidence, support, encouragement and cooperation in order to achieve the goals and objectives of the institution.  The research used a qualitative descriptive, informants in this study is the Principal and  Teachers at MIN 1 and MIN 2 Samarinda. Data were analyzed by following the model of the measures used by Miles and Huberman: data reduction, data display and conclusion. From the analysis of these data, we concluded that leadership styleis trans formational MIN 1 and MIN 2 Samarinda, it can be seen from the way the principal and teachers to transform the situation and habit schange, deliveringa sublime goal in the form of spiritual valueshigh, raise the value of freedom, justice and equality among teachers, giving the example of the teachers, teachers fostera desire to bring about the development of the school and develop a sense of discipline, responsibility, sincerity and zeal to work hard